Cleavage efficiencies of model substrates for ribonuclease P from Escherichia coli and Thermus thermophilus. - Schlegl, J (1992)
We compared cleavage efficiencies of mono-molecular and bipartite model RNAs as substrates for RNase P RNAs (M1 RNAs) and holoenzymes from E. coli and Thermus thermophilus, an extreme thermophilic eubacterium. Acceptor stem and T arm of pre-tRNA substrates are essential recognition elements for both enzymes. Impairing coaxial stacking of acceptor and T stems and omitting the T loop led to reduced cleavage efficiencies. Small model substrates were less efficiently cleaved by M1 RNA and RNase P from T. thermophilus than by the corresponding E. coli activities. Competition kinetics and gel retardation studies showed that truncated tRNA substrates are less tightly bound by RNase P and M1 RNA from both bacteria. Our data further indicate that (pre-)tRNA interacts stronger with E. coli than T. thermophilus M1 RNA. Thus, low cleavage efficiencies of truncated model substrates by T. thermophilus RNase P or M1 RNA could be explained by a critical loss of important contact points between enzyme and substrate. In addition, acceptor stem--T arm substrates, composed of two synthetic RNA fragments, have been designed to mimic internal cleavage of any target RNA molecule available for base pairing.